Philippa fisher and the fairy's promise - Kessler, Liz (Kessler, Liz. Philippa Fisher., 2015)
Philippa and her fairy godsister, Daisy, are asked by the High Counsel to go on a fantastic journey together to finda a missing fairy and preserve the portals that connect the fairy and human realms.